Research on Health Service System for the Elderly in Xinjiang - Wen Ma, Weimin Li, Jie Ma, Jiyang Yang (Forest Chemicals Review, 1970)
Xinjiang has been a multi-ethnic area since ancient times, with a vast area and a small population. According to the census results in recent years, the aging problem has become very prominent due to the rapid increase in the proportion of aging population in Xinjiang. As a result, the health care of the elderly has become a relatively complicated problem Relying solely on medical services or day care services can no longer meet the health needs of the elderly, which has become an unavoidable obstacle and bottleneck in the establishment of health service system. In this paper, the elderly in Xinjiang will be studied through field research and other research methods, to explore the elderly health service system in line with Xinjiang's cultural environment, food structure and many other local characteristics combined with the actual situation.